(3eHGOF GdEOGQI GdMOjKI GdGSGSjGJ (B- (3GdbhGYO (B- (3GdeaGgjes - (3YHO GdYdj(B, (3Ydj CHh GdThfs ((3YeGfs (3OGQ OLdI fGTQhf hehRYhfs, 2022)
(3eaghe GdEOGQI, GdbjGOI GdEOGQjI, bhGYO GdEOGQI, eaghe GJNGP GdbQGQGJ, CgejI GJNGP GdbQGQGJ hGdYhGed GdeDKQI ajg, CfhGY hfXQjGJ GJNGP GdbQGQGJ, eYhbGJ GJNGP GdbQGQGJ hJMSjf YedjI GJNGPgG, eGgjI EOGQI GdehGQO GdHTQjI, GdJWhQ GdJGQjNj dEOGQI GdehGQO GdHTQjI, JfXje hSjGSI EOGQI GdehGQO GdHTQjI, GSJQGJjLjI hJNWjW GdehGQO GdHTQjI, eGgjI EOGQI GdLhOI GdTGedI, eQGMd JWhQ EOGQI GdLhOI GdTGedI, CgejI heHGOF EOGQI GdLhOI GdTGedI, COhGJ heJWdHGJ JWHjb EOGQI GdLhOI GdTGedI, QhGO EOGQI GdLhOI GdTGedI, eGgjI GdJOQjH aj GdEOGQI, CgejI hCgOGa GdJOQjH aj GdEOGQI, CfhGY hCSGdjH GdJOQjH hGMjGLGJg, eHGOF hebheGJ GdJOQjH, GSJQGJjLjI GdJOQjH, eGgjI GSJQGJjLjI GdEOGQI, CgeSI hCgOGa GSJQGJjLjI GdEOGQI, GdJNWjW GdGSJQGJjLj ddEOGQI, GdGNJjGQ GdGSJQGJjLj, CYOGO GSJQGJjLjI EOGQI GdYGedjf(B.s
Keywords: (3GJNGP GdbQGQGJs; (3GOGQI GdCYeGds; (3GdEOGQIs; (3GdEOGQI(B- (3JWhjQs; (3GdJNWjW (B- (3JfXje hEOGQIs; (3GdJOQjH GdEOGQjs